Fitoterapia e plantas medicinais em unidades básicas de saúde no município de Itabaiana – Sergipe: a visão dos profissionais de saúde - Costa, Renata Rodrigues da (2022)
This study verified the use of medicinal plants and herbal medicines by doctors, nurses, dentists, pharmacists, Community Health Workers (CHW) who work in primary health care in Itabaiana/SE. This is a descriptive and exploratory study with a quantitativequalitative approach in which the data collection instrument was a questionnaire via google form, the variables were age, sex, education level and profession. The collected data were submitted to descriptive statistical analysis, percentage analysis using Microsoft Excel 2013® and also to Bardin's content analysis. A total of 37 professionals answered the questionnaire, (49% or 18) of the participants stated that they had no contact with the herbal theme during graduation and (41% or 15) answered that they do not know how to differentiate medicinal plants from herbal medicines, however, (94 % or 35) of the total sample of this study showed interest in implementing projects that encourage the use of medicinal plants and herbal medicines in the municipality. It is concluded that there was a lack of subjects and content related to the theme during the academic training of these professionals.